2017
DOI: 10.2217/imt-2016-0128
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab in The Treatment of Psoriasis: An Update

Abstract: Biological drugs are pharmaceuticals manufactured using biotechnology methods that may target specific cytokines, cytokine receptors or surface molecules, and modulate the immunological response of the organism. Psoriasis is a common cutaneous disease in which biological drugs have been evaluated and widely accepted in clinical practice. Secukinumab is a monoclonal antibody targeting IL-17A which has been extensively researched in clinical trials and registered in treating moderate to severe plaque psoriasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
1
18
0
2
Order By: Relevance
“…[13][14][15][16][17][18] Numerous clinical trials have shown that the proportion of patients achieving Psoriasis Area and Severity Index (PASI) 75 and PASI 90 response at week 12 was significantly higher in patients receiving secukinumab 300 mg compared to placebo (P < 0.001) 17,19,20 and etanercept (P < 0.001), 17 as well as compared to ustekinumab (P < 0.0001) at week 16 18 and at week 52. [13][14][15][16][17][18] Numerous clinical trials have shown that the proportion of patients achieving Psoriasis Area and Severity Index (PASI) 75 and PASI 90 response at week 12 was significantly higher in patients receiving secukinumab 300 mg compared to placebo (P < 0.001) 17,19,20 and etanercept (P < 0.001), 17 as well as compared to ustekinumab (P < 0.0001) at week 16 18 and at week 52.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18] Numerous clinical trials have shown that the proportion of patients achieving Psoriasis Area and Severity Index (PASI) 75 and PASI 90 response at week 12 was significantly higher in patients receiving secukinumab 300 mg compared to placebo (P < 0.001) 17,19,20 and etanercept (P < 0.001), 17 as well as compared to ustekinumab (P < 0.0001) at week 16 18 and at week 52. [13][14][15][16][17][18] Numerous clinical trials have shown that the proportion of patients achieving Psoriasis Area and Severity Index (PASI) 75 and PASI 90 response at week 12 was significantly higher in patients receiving secukinumab 300 mg compared to placebo (P < 0.001) 17,19,20 and etanercept (P < 0.001), 17 as well as compared to ustekinumab (P < 0.0001) at week 16 18 and at week 52.…”
Section: Introductionmentioning
confidence: 99%
“…Secukinumab, a fully human monoclonal antibody that selectively neutralizes IL-17A, has demonstrated superior and sustained efficacy in the treatment of moderate to severe psoriasis. [13][14][15][16][17][18] Numerous clinical trials have shown that the proportion of patients achieving Psoriasis Area and Severity Index (PASI) 75 and PASI 90 response at week 12 was significantly higher in patients receiving secukinumab 300 mg compared to placebo (P < 0.001) 17,19,20 and etanercept (P < 0.001), 17 as well as compared to ustekinumab (P < 0.0001) at week 16 18 and at week 52. 21 Secukinumab is approved in Germany since 2015 for moderate to severe psoriasis, psoriatic arthritis and ankylosing spondylitis.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of these cells promotes the release of inflammatory cytokines and induces pathological processes in several tissues: vessel activation, matrix destruction, cartilage damage, and bone erosion (5,6). Secukinumab is a human IgG1 monoclonal antibody that selectively binds and neutralizes IL-17A (7,8). Its efficacy in chronic plaque psoriasis has been demonstrated by several clinical trials and secukinumab has recently been approved for the treatment of psoriatic arthritis in adults, alone or in association with methotrexate (MTX) when the response to previous DMARDs is inadequate (7).…”
Section: Secukinumab Treatment In Psoriatic Patients: Italian Experiementioning
confidence: 99%
“…Secukinumab is a human IgG1 monoclonal antibody that selectively binds and neutralizes IL-17A (7,8). Its efficacy in chronic plaque psoriasis has been demonstrated by several clinical trials and secukinumab has recently been approved for the treatment of psoriatic arthritis in adults, alone or in association with methotrexate (MTX) when the response to previous DMARDs is inadequate (7). Articles published in this supplement report clinical experiences in the use of secukinumab in different psoriasis variants.…”
Section: Secukinumab Treatment In Psoriatic Patients: Italian Experiementioning
confidence: 99%
“…В 2016 г. в России был зарегистрирован первый биологический препарат, направленный на блокаду ИЛ-17,секукинумаб производства компании Новартис Фарма АГ (Швейцария), который представляет собой полностью человеческое антитело (IgG1), селективно связывающее и нейтрализующее ИЛ-17А [12,16]. По результатам регистрационных исследований III фазы секукинумаба у пациентов со среднетяжелым и тяжелым вульгарным псориазом порядка 80% пациентов достигли PASI 75 (первичной конечной точки) к 12-й неделе лечения, также препарат продемонстрировал превосходство над этанерцептом и устекинумабом [12,24]. С 2011 г. в российской биотехнологической компании «БИОКАД» велась разработка собственного оригинального моноклонального антитела против ИЛ-17.…”
Section: Introductionunclassified